2006
DOI: 10.5006/1.3280670
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbide Precipitation and Rolling Direction on Intergranular Stress Corrosion Cracking of Austenitic Stainless Steels in Hydrogenated High-Temperature Water

Abstract: The intergranular stress corrosion cracking (IGSCC) growth behavior of austenitic stainless steels (SS) in hydrogenated high-temperature water were studied using compact tension specimens (0.5T for cold-worked materials). The effects of carbide precipitation, alloy composition, and the cold rolling direction on crack growth behavior were studied. Then, to examine these infl uences on IGSCC, grain boundary sliding was studied in high-temperature air. The similar dependences of carbide precipitation, cold work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…So grain boundary carbides seem to have detrimental effect in SCC growth due to the enhanced local strains near grain boundaries. Interestingly, the crack growth rates of T-S orientated cold rolled stainless steel in 320°C simulated primary water from Arioka et al [35] still reveal the mitigating effect of carbide precipitation. This seemingly conflicting result attests to the orientation dependence of SCC susceptibility of cold rolled material with carbide precipitation.…”
Section: Effect Of Grain Boundary Carbidesmentioning
confidence: 95%
“…So grain boundary carbides seem to have detrimental effect in SCC growth due to the enhanced local strains near grain boundaries. Interestingly, the crack growth rates of T-S orientated cold rolled stainless steel in 320°C simulated primary water from Arioka et al [35] still reveal the mitigating effect of carbide precipitation. This seemingly conflicting result attests to the orientation dependence of SCC susceptibility of cold rolled material with carbide precipitation.…”
Section: Effect Of Grain Boundary Carbidesmentioning
confidence: 95%
“…However, more recent reports indicated that cold-worked austenitic steels are susceptible to SCC in hydrogenated water conditions and several explanations have been proposed [2,4,8,16,20,58,60]. This research will focus on clarifying whether cold work accelerates crack growth by changing the mechanical properties, the corrosion behaviour, or both.…”
Section: Introductionmentioning
confidence: 92%
“…XRD results suggested that an increasing Cr concentration tended to change the Fe-rich spinel oxide from Fe 3 O 4 to FeCr 2 O 4 . Arioka found that Cr content in austenitic stainless steels greatly influences crack growth rate under PWR primary water conditions [8]. It is still not clear whether this is caused by a change in corrosion resistance, a change in mechanical properties (via the SFE) or both.…”
Section: Influence Of Cr Content On Oxidation and Scc Crack Growthmentioning
confidence: 98%
“…Recent researches have indicated that the intergranular SCC (IGSCC) growth rate of non-sensitized SUS316 depends on the level of the cold work (CW). [1][2][3][4][5][6][7] It suggested that the plastic strain introduced by CW process induced the concentration of the internal stress around the grain boundary. Observation of the inhomogeneous distribution of internal stress in grains is necessary for clarifying the mechanism of IGSCC in nonsensitized SUS316.…”
Section: Introductionmentioning
confidence: 99%